An enhanced CRISPR repressor for targeted mammalian gene regulation - Yeo, NC; Chavez, A; Lance-Byrne, A; Chan, Y; Menn, D; Milanova, D; Kuo, C-C; Guo, X; Sharma, S; Tung, A; Cecchi, RJ; Tuttle, M; et al. (Springer Nature, 2018)
The RNA-guided endonuclease Cas9 can be converted into a programmable transcriptional repressor, but inefficiencies in target-gene silencing have limited its utility. Here we describe an improved Cas9 repressor based on the C-terminal fusion of a rationally designed bipartite repressor domain, KRAB–MeCP2, to nuclease-dead Cas9. We demonstrate the system’s superiority in silencing coding and noncoding genes, simultaneously repressing a series of target genes, improving the results of single and dual guide RNA library screens, and enabling new architectures of synthetic genetic circuits.